Interventions to improve employee health and well‐being within health care organizations: A systematic review. Issue 4 (8th November 2017) - Williams, Stephen P.; Malik, Humza T.; Nicolay, Christopher R.; Chaturvedi, Sankalp; Darzi, Ara; Purkayastha, Sanjay
Abstract: In response to an increasing body of evidence on the importance of employee health and well‐being (HWB) within health care, there has been a shift in focus from both policymakers and individual organizations toward improving health care employee HWB. However, there is something of a paucity of evidence regarding the impact and value of specific HWB interventions within a health care setting. The aim of this article was to systematically review the literature on this topic utilizing the EMBASE, Global Health, Health Management Information Consortium, MEDLINE, and PsycINFO databases. Forty‐four articles were identified and, due to a large degree of heterogeneity, were considered under different headings as to the type of intervention employed: namely, those evaluating changing ways of working, physical health promotion, complementary and alternative medicine, and stress management interventions, and those utilizing multimodal interventions . Our results consider both the efficacy and reliability of each intervention in turn and reflect on the importance of careful study design and measure selection when evaluating the impact of HWB interventions.